Novel Mutation in PLA2G6 Gene in a Patient with Infantile Neuroaxonal Dystrophy - Veerapandiyan, Aravindhan; Chaudhari, Amit; Aravindhan, Akilandeswari; Hayes-Rosen, Caroline (Journal of Pediatric Neurology, 2017)
Infantile neuroaxonal dystrophy (INAD) is an autosomal recessive disorder that causes psychomotor regression. Clinicopathological features include truncal hypotonia followed by spastic quadriparesis, strabismus, nystagmus, cerebellar ataxia, bulbar dysfunction, and cerebellar atrophy. INAD is associated with a variety of mutations in the PLA2G6 gene that encodes the group VI calcium-independent phospholipase A2 protein which is important in cell membrane homeostasis. Defects in this protein cause axonal dystrophy. We report a 2-year-old boy with INAD who was found to have a novel deletion c.1019_1025del7 leading to a frame shift in the PLA2G6 gene. We suggest that this change may be an addition to the array of mutations causing INAD.
Keywords: developmental regression; delay; neuroaxonal dystrophy; PLA2G6